The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-08987-8
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition analysis of polyhedra matrix of Bombyx mori nucleopolyhedrovirus (BmNPV) showed powerful capacity of polyhedra to encapsulate foreign proteins

Abstract: Polyhedra can encapsulate other proteins and have potential applications as protein stabilizers. The extremely stable polyhedra matrix may provide a platform for future engineered micro-crystal devices. However, the protein composition of the polyhedra matrix remains largely unknown. In this study, the occlusion-derived virus (ODV)-removed BmNPV polyhedra matrix fraction was subjected to SDS-PAGE and then an LC-ESI-MS/MS analysis using a Thermo Scientific Q Exactive mass spectrometer. In total, 28 host and 91 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 201 publications
0
4
0
Order By: Relevance
“…It was also shown that OBs could not be formed by fusing proteins to polyhedrin, except in the presence of wild‐type virus (Sampieri et al, 2015). We detected 28 host proteins and 91 viral proteins embedded inside BmNPV OBs (Guo et al, 2017). These results indicate that the assembly of OBs is a complicated and well‐regulated process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that OBs could not be formed by fusing proteins to polyhedrin, except in the presence of wild‐type virus (Sampieri et al, 2015). We detected 28 host proteins and 91 viral proteins embedded inside BmNPV OBs (Guo et al, 2017). These results indicate that the assembly of OBs is a complicated and well‐regulated process.…”
Section: Discussionmentioning
confidence: 99%
“…The autophagosome was labeled mCherry fused with marker BmLC3 pathogenesis (Furlong & Hwang, 2019;Ke, 2018). It has been reported BmNPV infection induced autophagy in host cells (Wang et al, 2017). Polyhedrin directly interacts with LC3, and inhibition of autophagy by 3-methyladenine (3-MA) decreased polyhedrin expression and OB production (Guo et al, 2015).…”
Section: Nedd8 Colocalizes With Aggresome and Autophagosomementioning
confidence: 99%
“…The N-terminal 50 amino acids of polyhedrin represents the recognition signal necessary for foreign protein incorporation, and the N-terminal 100 amino acids of polyhedrin allowed for the most efficient protein incorporation into polyhedral occlusion bodies . The protein encoded by ORF 134 of BmNPV has also been shown to be a suitable fusion partner for OBD (Guo et al, 2017).…”
Section: Occlusion Bodymentioning
confidence: 99%
“…The N-terminal 50 amino acids of polyhedrin represents the recognition signal necessary for foreign protein incorporation, and the N-terminal 100 amino acids of polyhedrin allowed for the most efficient protein incorporation into polyhedral occlusion bodies (Chen et al, 2013). The protein encoded by ORF 134 of BmNPV has also been shown to be a suitable fusion partner for OBD (Guo et al, 2017).…”
Section: Occlusion Bodymentioning
confidence: 99%